Inner southern magnetosphere observation of Mercury via SERENA ion sensors in BepiColombo mission - S. Orsini; A. Milillo; H. Lichtenegger; A. Varsani; S. Barabash; S. Livi; E. De Angelis; T. Alberti; G. Laky; H. Nilsson; M. Phillips; A. Aronica; et al. (Nature Communications, 2022)
Abstract Mercury’s southern inner magnetosphere is an unexplored region as it was not observed by earlier space missions. In October 2021, BepiColombo mission has passed through this region during its first Mercury flyby. Here, we describe the observations of SERENA ion sensors nearby and inside Mercury’s magnetosphere. An intermittent high-energy signal, possibly due to an interplanetary magnetic flux rope, has been observed downstream Mercury, together with low energy solar wind. Low energy ions, possibly due to satellite outgassing, were detected outside the magnetosphere. The dayside magnetopause and bow-shock crossing were much closer to the planet than expected, signature of a highly eroded magnetosphere. Different ion populations have been observed inside the magnetosphere, like low latitude boundary layer at magnetopause inbound and partial ring current at dawn close to the planet. These observations are important for understanding the weak magnetosphere behavior so close to the Sun, revealing details never reached before.